Pengaruh Pelatihan, Pengembangan Karir dan Disiplin Kerja terhadap Kinerja Pegawai KPP Pratama Surabaya Mulyorejo - Rahmadhan, Widiarto; Kuswandi, Kuswandi; Rahayu, Sri (Syntax Corporation, 2025)
This research tests and analyzes Training (X1), Career Development (X2), and Work Discipline (X3) which simultaneously influence Employee Performance (Y) at KPP Pratama Surabaya Mulyorejo. The population used in this research were all employees at KPP Pratama Surabaya Mulyorejo, totaling 108 people consisting of 95 Executives and Functionals, 2 Supervisors, 10 Section Heads, and 1 Head of Office. The sampling technique used is simple random sampling technique, which is a random sample selection method where all members of the population have the same opportunity to be sampled. Sampling was taken using the Slovin formula calculation and the results obtained were 77 respondents, namely KPP Pratama Surabaya Mulyorejo employees. The analytical tool used is multiple linear regression with the help of SPSS 21.0 software. This research makes a unique contribution by focusing on the specific context of KPP Pratama Surabaya Mulyorejo. While numerous studies have examined the relationship between training, career development, work discipline, and employee performance, this study fills a gap in the literature by analyzing these phenomena within the context of a government institution, particularly in the tax environment. Consequently, the findings of this study are expected to provide more relevant recommendations for improving employee performance at KPP Pratama Surabaya Mulyorejo. The research results show that Training (X1), Career Development (X2), and Work Discipline (X3) have a simultaneous and partial effect on Employee Performance (Y) at KPP Pratama Surabaya Mulyorejo.